EVALUASI PENERAPAN AKUNTANSI PIUTANG LEASING DAN PELAPORANNYA PADA PT. ASTRA SEDAYA FINANCE DI MANADO - Tulangow, Erill Armando; Elim, Inggriani; Pusung, Rudy J. (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
The emergence of leasing institutions is an attractive alternative for entrepreneurs, because currently they use cash in cash for the companys operational activities. Through the lease they can generate funds to finance the purchase of goods with a term between three years to five years or more. The object of this research is PT. Astra Sedaya Finance Manado which is the largest automotive financing company in Indonesia. The purpose of this study is to analyze the accountability of Astra Sedaya Finance in Manado. The method used with descriptive method, with data data being used with. Which will be leased, the system of recording and reporting of leasing transactions evaluate the advantages / disadvantages of the application of accounting for lease transactions and reporting of lease transactions, and draw conclusions. The results can be seen that leasing has several types and classification and criteria to determine the accounting system. The application of accounting and reporting for lease transactions at PT Astra Sedaya Finance uses a system capital lease whereby the lease may transfer ownership at the end of the lease term. Based on aspects of Recording, reporting and disclosure, the accounting treatment of leases at PT Astra Seaya Finance is in conformity with the applicable PSAK.Keywords : Leasing, Leasing Receivable Accounting, PSAK No.30